2014
DOI: 10.1111/luts.12080
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selective Prostaglandin E2 EP2 Receptor Agonist CP‐533,536 on Voiding Efficiency in Rats with Midodrine‐Induced Functional Urethral Obstruction

Abstract: These results suggest that a selective EP2 receptor agonist could ameliorate the elevation of RV and improve the reduction of VE in rats with functional urethral obstruction caused by stimulation of α1 -adrenoceptors. The mechanism of action might be not potentiation of bladder contraction but rather preferential relief of urethral constriction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…CP‐533,536 dose‐dependently decreased perfusion pressure, but had no effect on maximum voiding pressure, intercontraction interval, or intravesical threshold pressure. In conscious rats, where midodrine markedly increased residual volume, and reduced VE, CP‐533,536 dose‐dependently counteracted these effects …”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…CP‐533,536 dose‐dependently decreased perfusion pressure, but had no effect on maximum voiding pressure, intercontraction interval, or intravesical threshold pressure. In conscious rats, where midodrine markedly increased residual volume, and reduced VE, CP‐533,536 dose‐dependently counteracted these effects …”
Section: Methodsmentioning
confidence: 97%
“…In spinal cord injured (SCI) rats, Wada et al found that the PGE2‐induced activation of EP1 receptors in the spinal cord contributes to the initiation of bladder over activity, and concluded that the EP1 receptor could be a therapeutic target for the treatment of neurogenic DO due to SCI. The selective EP2 receptor agonist, CP‐533,536, was tested on voiding efficiency (VE) in anesthetised rats with functional urethral obstruction, induced by midodrine . CP‐533,536 dose‐dependently decreased perfusion pressure, but had no effect on maximum voiding pressure, intercontraction interval, or intravesical threshold pressure.…”
Section: Methodsmentioning
confidence: 99%
“…All surgical procedures and measurement of micturition parameters via cystometry were performed based on a previously described method. 19,20 Briefly, a catheter (PE-160; Becton, Dickinson & Co., Franklin Lakes, NJ, USA) for saline infusion into the bladder and collection of residual urine after voiding was inserted into the bladder and connected to a pressure transducer (DX-100; Nihon Kohden, Tokyo, Japan) and infusion pump (TE-331S, STC-528; Terumo Co., Tokyo, Japan) via a three-way tap. Each rat was placed in a Ballman's cage (Natsume Seisakusho Co., Ltd., Tokyo, Japan).…”
Section: Evaluation Of Voiding Function In Rats With Voiding Dysfunct...mentioning
confidence: 99%
“…We hypothesize that a considerable number of patients suffering from lower urinary tract symptoms with various possible pathophysiologies including aging 30 have such a condition but are left underdiagnosed because of a lack of clear urodynamically confirmed DU or BOO. 31 We pharmacologically reproduced this condition by administering a combination of atropine and midodrine at doses lower than those used in previous studies, 19,32,33 and applying the experimental methods we used previously 19,20 (Figure 3). In this model, we used the effects of distigmine at 0.003 mg/kg iv as a benchmark because it significantly enhanced the PNS-induced elevation of IVP (Figure 2C) at the plasma concentration similar to that of the clinically efficacious dose (15 mg/man/d) 34,35 (data not shown).…”
Section: Number Of Stoolsmentioning
confidence: 99%